Koleksi hadits hadits hukum (al ahkamun nabawiyyah) - T.M. Hasbi Ash-Shiddieqy (Al Ma'arif, 1976)
Oen, Jil. 1=c.1-4;Jil. 2=c.1;Jil. 5=c.1-2; Jil. 6=c.1-7/ast jil.2 =c.2/ast jil.1 =c.5/ir, jil.1,c.6; sn,jl.1,c.7/ tr, jil.1=c.8; jil.3=c.1/tr, jil.5=c.4-5/ir, jil.1,c.9-10/ tr, jil.5=c.6/tr, jil.6=c.8/tr, jil.1=c.11; jil.5=c.7-8; jil.2=c.3-4